Digital Pancasila : Strategi Komunikasi dalam Mempromosikan Nilai-Nilai Kebangsaan di Era Media Sosial - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Adiningrum Dwi Nugraheni; Muhammad Rasyid Ridho; Muhammad Arifin Aprilianto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The digital era has brought significant changes in societal communication patterns, including the dissemination of national values. Pancasila, as the ideology of Indonesia, faces new challenges and opportunities amidst the rise of social media as a primary communication platform. This study analyzes digital communication strategies for promoting Pancasila values through social media platforms. Using a qualitative approach, the research explores various effective communication methods to enhance public awareness and participation in national values. The findings indicate that interactive content-based strategies, collaboration with stakeholders, and the utilization of social media algorithms can improve the effectiveness of Pancasila value dissemination. The study concludes by emphasizing the importance of adapting communication strategies to digital technological developments to ensure national values remain relevant and embraced by younger generations.